The Use of Cotton Seed Husk Waste as Organic Compost to Support Sustainable Agriculture in Dalaka Village, Donggala Regency: Penelitian - Dewi; Mery Napitupulu (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The village of Dalaka in Donggala Regency has abundant potential for kapok cultivation, which the community utilises as an economic resource through the use of kapok fibre. However, kapok fruit husks are not yet being utilised to their full potential and are generally discarded or burnt, thereby posing a potential risk of environmental pollution. This community service initiative aims to enhance the community’s knowledge and skills in processing kapok husk waste into organic compost as part of efforts to support sustainable agriculture. The implementation methods included assessing the village’s potential, coordinating with the village government, awareness-raising sessions, compost-making demonstrations, discussions, and activity evaluation. The activity was attended by 27 participants comprising farmer groups, villagers, and local youth. The results showed that 88.9% of participants understood the stages of compost production and 77.8% were able to independently replicate the compost-making process. Furthermore, 92.6% of participants expressed an interest in applying organic compost to their farmland. This activity has had a positive impact on raising community awareness regarding the management of agricultural waste using local resources. The utilisation of cotton seed husk waste as organic compost has the potential to serve as an environmentally friendly solution to reduce organic waste whilst simultaneously enhancing soil fertility in a sustainable manner.